Chemical Composition and In-vitro Antibacterial Activity of the Essential Oil of Nigerian Moringa oleifera Lam. Flowers - Balogun, O.S.; Fadare, R.Y.; Fadare, O.A.; Akinpelu, D.A.; Obafemi, C.A. (SCIENCEDOMAIN international, 2018)
10